Prevalence of Medical Emergencies and Dentists’ Knowledge of Their Management in Dental Clinics in Libya: A Cross-Sectional Study - Hana Albasheer Abduljalil (Khalij-Libya Journal of Dental and Medical Research, 2026)
Medical emergencies (MEs) are sudden and critical health conditions that may threaten patients ‘lives or well-being if not immediately managed. Libya exhibits a significant deficiency in data about the preparedness of dental professionals to deal with medical emergencies. To evaluate the frequency of medical emergencies occurring in dentistry clinics in Libya. A cross-sectional study was conducted over 12-24 weeks among 148 licensed dentists practicing in public and private clinics across five major Libyan cities. Data were collected using a structured, self-administered electronic questionnaire covering demographic characteristics, history and types of medical emergencies encountered, knowledge of emergency management (including syncope, hypoglycemia, anaphylaxis, and cardiac arrest), and training and preparedness indicators, such as the availability of emergency kits. Data were analyzed utilizing SPSS version 26. Among the 148 dentists, 60.8% had received undergraduate training in medical emergency management, but only 20.3% had received recent training within the last year, and 45.3% had attended post-graduate workshops. Basic Life Support was the most common training (43.2%). A total of 70.9% expressed the need for further training, and 53.4% reported the absence of emergency protocol sheets in their clinics. Regarding confidence, 66.2% were either extremely (32.4%) or very confident (33.8%) in interpreting vital signs. For minor emergencies, 62.9% felt fully capable (20.3%) or capable enough (42.6%), whereas confidence declined for serious emergencies, with 60.2% reporting being not capable enough (48.0%) or not able at all (12.2%). Concerning emergency drugs, only 10.8% were extremely confident, while 68.3% were somewhat (41.2%) or not so confident (27. 1%). Emergency equipment was lacking in 42.6% of clinics, and 68.9% of dentists reported encountering 1–2 medical emergencies over the past five years. Medical emergencies are relatively common in Libyan dental clinics. Despite the high prevalence of emergency exposure, there is a significant lack of knowledge, preparedness, and confidence among dentists. Strengthening undergraduate curricula, implementing mandatory continuing professional development programs, and promoting regular hands-on BLS and simulation-based training are important to enhance emergency readiness and improve patient safety in dental practice in Libya.